'What is infrastructure? What does it do?': anthropological perspectives on the workings of infrastructure(s). (1st March 2022) - Kanoi, Lav; Koh, Vanessa; Lim, Al; Yamada, Shoko; Dove, Michael R
Abstract: Infrastructure is often thought of in big material terms: dams, buildings, roads, and so on. This study, instead, draws on literatures in anthropology and the social sciences to analyse infrastructures in relation to society and environment, and so cast current conceptions of infrastructure in a new light. Situating the analysis in context of President Biden's recent infrastructure bill, the paper expands what is meant by and included in discussions of infrastructure. The study examines what it means for different kinds of material infrastructures to function (and for whom) or not, and considers how the immaterial infrastructure of human relations are manifested in, for example, labour, as well as how infrastructures may create intended or unintended consequences in enabling or disabling social processes. Further, in this study, we examine concepts embedded in thinking about infrastructure such as often presumed distinctions between the technical and the social, nature and culture, the human and the non-human, and the urban and the rural, and how all of these are actually implicated in thinking about infrastructure. Our analysis, thus, draws from a growing body of work on infrastructure in anthropology and the social sciences, enriches it with ethnographic insights from our own field research, and so extends what it means to study 'infrastructures' in the 21st century.